Performance-based testing for ICT skills assessing: a case study of students and teachers’ ICT skills in Finnish schools - Kaarakainen Meri-Tuulia; Kivinen Osmo; Vainio Teija (Springer Berlin Heidelberg, 2022)
Skills enabling and ensuring universal access to information have been investigated intensively during the past few years. The research results provide knowledge on the differences and digital divides. When examining ICT skill levels, the accuracy of assessment is one of the key issues to address the results and gain the applicable data for appropriate interventions to enhance digital inclusion. To date, ICT skill assessment is based mainly on self-reports and subjective evaluations. However, as previous studies have shown, people tend to overrate or underrate their own levels of competence. Thus, novel performance-based approach for assessing ICT skills is presented in this paper. The ICT skill test contains 42 tasks grouped into 17 ICT fields. The study was conducted with upper comprehensive and upper secondary level school students (n = 3159) and their teachers (n = 626) during years 2014–2016 in Finland. Using factor analysis, three ICT skills factors were created: basic digital skills, advanced technical skills, and professional ICT skills. The performance in the ICT skill test was also divided by gender, as the male students and teachers outperformed the female students and teacher. Outperformance also occurred by educational level, as both upper secondary level students and teachers were seen as possessing higher-level ICT skills than students and teachers at the comprehensive level. We thus argue that to compare the ICT skills and the validity of the assessments, we needed to ensure consistent assessment for both students and teachers. In addition, in order to diminish the ICT skill gap among students, interventions using formal education are urgently needed, and in particular, more attention should be given to both teacher training and in-service training.